Mechanical power and normalized mechanical power in pediatric acute respiratory distress syndrome - Shaikh, Farhan A. R.; Ramaswamy, Karthik N.; Chirla, Dinesh K.; Venkataraman, Shekhar T.; Kneyber, Martin C. J. (Frontiers in Pediatrics, 2024)
Background Mechanical power (MP) refers to the energy transmitted over time to the respiratory system and serves as a unifying determinant of ventilator-induced lung injury. MP normalization is required to account for developmental changes in children. We sought to examine the relationship between mechanical energy (MEBW), MP normalized to body weight (MPBW), and MP normalized to respiratory compliance (MPCRS) concerning the severity and outcomes of pediatric acute respiratory distress syndrome (pARDS). Method In this retrospective study, children aged 1 month to 18 years diagnosed with pARDS who underwent pressure-control ventilation for at least 24 h between January 2017 and September 2020 were enrolled. We calculated MP using Becher's equation. Multivariable logistic regression analysis adjusted for age, pediatric organ dysfunction score, and oxygenation index (OI) was performed to determine the independent association of MP and its derivatives 24 h after diagnosing pARDS with 28-day mortality. The association was also studied for 28 ventilator-free days (VFD-28) and the severity of pARDS in terms of OI. Results Out of 246 admitted with pARDS, 185 were eligible, with an overall mortality of 43.7%. Non-survivors exhibited higher severity of illness, as evidenced by higher values of MP, MPBW, and MEBW. Multivariable logistic regression analysis showed that only MEBW but not MP, MPBW, or MPCRS at 24 h was independently associated with mortality [adjusted OR: 1.072 (1.002–1.147), p = 0.044]. However, after adjusting for the type of pARDS, MEBW was not independently associated with mortality [adjusted OR: 1.061 (0.992–1.136), p = 0.085]. After adjusting for malnutrition, only MP at 24 h was found to be independently associated. Only MPCRS at 1–4 and 24 h but not MP, MPBW, or MEBW at 24 h of diagnosing pARDS was significantly correlated with VFD-28. Conclusions Normalization of MP is better related to outcomes and severity of pARDS than non-normalized MP. Malnutrition can be a significant confounding factor in resource-limited settings.